Synthesis of Nano-Pore Size Ag(I)-Imprinted Polymer for the Extraction and Preconcentration of Silver Ions Followed by Its Determination with Flame Atomic Absorption Spectrometry and Spectrophotometry Using Localized Surface Plasmon Resonance Peak of Silver Nanoparticles - Dadfarnia,Shayessteh (2015)
Silver ion imprinted polymer (IIP) was synthesized in the presence of Ag(I)-N,N’‑bis(salicylidene)ethylenediamine (salen) complex using 4-vinylpyridine as the functional monomer, ethylene glycol dimethacrylate (EGDMA) as the crosslinker, and 2,2-azobis(isobutyronitrile) (AIBN) as the initiator. The Ag(I)-imprinted polymer (IIP) particles were characterized by SEM (scanning electron microscope), FTIR (Fourier transform infrared spectroscopy) and BET/BJH (Brunauer-Emmett-Teller/Barrett-Joyner-Halenda) analysis. The imprinted Ag(I) ions were completely removed by leaching the IIP with thiourea (0.5 mol L-1). The polymer was employed as a selective sorbent for extraction and separation of the trace amounts of the Ag(I) ions. The preconcentrated ion was determined via the flame atomic absorption spectrometry (FAAS) or it was reduced to silver nanoparticles and quantified by spectrophotometry based on its localized surface plasmon resonance peak (LSPRP). The figures of merit of both methods were compared. Under the optimized conditions, a sample volume of 80 mL resulted in an enhancement factor of 312. The detection limit (3Sb/m) and the relative standard deviation (n = 10) at 10 µg L-1 level for FAAS were found to be 0.06 µg L-1, 2.9%, whereas for the LSPRP method they were 0.5 µg L-1 and 10.3%, respectively. The methods were successfully applied to the determination of silver in radiology film, hair, nails, and water samples.